Bio-Based Flame-Retardant Systems for Polymers Obtained via Michael 1,4-Addition - Kamila Salasinska; Mateusz Barczewski; Mikelis Kirpluks; Ralfs Pomilovskis; Paweł Sulima; Sławomir Michałowski; Patryk Mietliński; Jerzy Andrzej Przyborowski; Anna Boczkowska (Molecules)
Phosphorus flame retardants react with cellulose hydroxyl groups via esterification, enhancing the effectiveness of char formation, which is beneficial in terms of the search for bio-sourced flame retardants. The current work assessed the flammability of a new polymer synthesized by Michael 1,4-addition (rP) and modified with developed intumescent flame retardant systems (FRs), in which lignocellulose components, such as sunflower husk (SH) and peanut shells (PS), replaced a part of the synthetic ones. The thermal and thermomechanical properties of the rP, with 20 wt.% each from six FRs, were determined by thermogravimetric analysis (TG), differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA). Moreover, the flammability and evolved gas were studied with pyrolysis combustion flow calorimetry (PCFC) and thermogravimetric analysis connected with Fourier transform infrared spectroscopy tests (TGA/FT-IR). The effects were compared to those achieved for unmodified rP and a polymer with a commercially available intumescent flame retardant (IFR). The notable improvement, especially in terms of the heat release rate and heat release capacity, indicates that the system with melamine phosphate (MP) and peanut shells (PS) can be used to decrease the flammability of new polymers. An extensive analysis of the composition and geometry of the ground shells and husk particles preceded the research.